EFFECT OF PROTEIN BOUND AND FREE LYSINE ON GROWTH PERFORMANCE, MEAT QUALITY, BLOOD HEMATOLOGY AND ECONOMICS IN BROILERS - Muhammad Arslan Asif; Muhammad Mahboob Ali Hamid; Muhammad Shoaib; Muhammad Aslam Mirza; Hafiz Hassan Iqbal; Muhammad Issa Khan; Najam-us-Sahar; Shahzad Ashraf; Muhammad Mansoor Javed; Soban Shehzad; Muhammad Salman Asif; Saad Jameel (Journal of Animal and Plant Sciences, 2023)
The objective of this study was study the protein bound and free lysine (Lys) on production performance in broilers. Two hundred and sixteen (216) day-old broiler chicks were distributed into three treatments, six replicates and 12 birds in each. Three isonitrogenous (CP 22.5%) and isocaloric (ME 3000 Kcal/kg) experimental diets were formulated. In control diet, total digestible Lys (1.20%) was contributed by feed ingredients like soybean meal, canola meal and fish meal. In other two diets, out of 1.2, 0.06 was free Lys that was either contributed by L-Lys Sulfate or L-Lys HCl which were assumed to be 100% digestible. Feed intake was (P≤0.05) lower in birds received free Lys than those reared on bounded Lys. Weight gain and FCR were improved (P≤0.05) in birds received protein bound Lys and free Lys as L-Lys Sulfate than L-Lys HCl. Dressing percentage, liver weight, water holding capacity, pH, cooking loss and blood hematology parameters were not affected by treatments. Production cost per kg live weight was lower in birds received free Lys as L-Lys Sulfate than others treatments. It can be concluded that use of free Lys in the form of L-Lys Sulfate had improved feed efficiency and economics efficiency without having negative effect on meat quality and blood hematology parameters.
Keywords: Bounded Lysine; Free Lysine; Growth performance; Blood hematology; Economics